Identification and genetic characterization of Saprolegnia parasitica , isolated from farmed and wild fish in Finland - Christine Engblom; Lotta Landor; Conny Sjöqvist; Tiina Korkea‐aho; Satu Viljamaa‐Dirks; Lars Paulin; Tom Wiklund (Journal of Fish Diseases, 2023)
Oomycete infections in farmed fish are one of the most significant disease issues in salmonid aquaculture worldwide. In the present study, Saprolegnia spp. in different farmed fish species in Finland were identified, and the molecular epidemiology of especially Saprolegnia parasitica was examined. We analysed tissue samples from suspected oomycete‐infected salmonids of different life stages from a number of fish farms, as well as three wild salmonids. From collected oomycete isolates, the ITS1, 5.8S and ITS2 genomic regions were amplified, analysed phylogenetically and compared with corresponding sequences deposited in GenBank. Of the sequenced isolates, 91% were identified as S. parasitica . Isolates of yolk sac fry were identified as different Saprolegnia spp. Among the isolates from rainbow trout eggs Saprolegnia diclina dominated. In order to determine potential dominating clones among the S. parasitica , isolates were analysed using Multi Locus Sequence Typing (MLST). The results showed that one main clone contained the majority of the isolates. The MLST analysis showed four main sequence types (ST1–ST4) and 13 unique STs. This suggests that the Saprolegnia infections in farmed fish in Finland are not caused by different strains originating in the farm environment. Instead, one main clone of S. parasitica is present in Finnish fish farms.

Reversible mutations in gliding motility and virulence genes: A flexible and efficient phage defence mechanism in Flavobacterium psychrophilum - Jóhanna Jørgensen; Krister Sundell; Daniel Castillo; Liv S. Dramshøj; Natasja B. Jørgensen; Susie B. Madsen; Lotta Landor; Tom Wiklund; Valentina L. Donati; Lone Madsen; Inger Dalsgaard; Mathias Middelboe (Environmental Microbiology, 2022)
Flavobacteria are among the most important pathogens in freshwater salmonid aquaculture worldwide. Due to concerns regarding development of antibiotic resistance, phage therapy has been proposed as a solution to decrease pathogen load. However, application of phages is challenged by the development of phage resistance, and knowledge of the mechanisms and implications of phage resistance is therefore required. To study this, 27 phage‐resistant isolates of F. psychrophilum were genome sequenced and characterized to identify genetic modifications and evaluate changes in phenotypic traits, including virulence against rainbow trout. Phage‐resistant isolates showed reduction or loss of gliding motility, proteolytic activity, and adhesion to surfaces, and most isolates were completely non‐virulent against rainbow trout fry. Genomic analysis revealed that most phage‐resistant isolates had mutations in genes associated with gliding motility and virulence. Reversal of these mutations in a sub‐set of isolates led to regained motility, proteolytic activity, virulence and phage susceptibility. Although costly, the fast generation of phage resistance driven by single, reversible mutations likely represents a flexible and efficient phage defence mechanism in F. psychrophilum . The results further suggest that phage administration in aquaculture systems to prevent F. psychrophilum outbreaks selects for non‐virulent phage‐resistant phenotypes.

Genome‐informed approach to identify genetic determinants of Flavobacterium psychrophilum phage susceptibility - Castillo Daniel; Jørgensen Johanna; Sundell Krister; Madsen Lone; Dalsgaard Inger; Wiklund Tom; Middelboe Mathias (Environmental Microbiology, 2021)
Summary The fish pathogen Flavobacterium psychrophilum infects farmed salmonids worldwide, and application of bacteriophages has been suggested for controlling disease outbreaks in aquaculture. Successful application of phages requires detailed knowledge about the variability in phage susceptibility of the host communities. In this study, we analysed the genetic diversity of F. psychrophilum hosts and phages from the Baltic Sea area to identify genetic determinants of phage‐host interaction patterns. A host range analysis of 103 phages tested against 177 F. psychrophilum strains (18 231 phage–host interactions) identified nine phage clusters, infecting from 10% to 91% of the strain collection. The core genome‐based comparison of 35 F. psychrophilum isolates revealed an extremely low overall genomic diversity (>99.5% similarity). However, a small subset of 16 ORFs, including genes involved in the type IX secretion system (T9SS), gliding motility and hypothetical cell‐surface related proteins, exhibited a highly elevated genetic diversity. These specific genetic variations were linked to variability in phage infection patterns obtained from experimental studies, indicating that these genes are key determinants of phage susceptibility. These findings provide novel insights on the molecular mechanisms determining phage susceptibility in F. psychrophilum and emphasizes the importance of phages as drivers of core genomic diversity in this pathogen.

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

Life history inhomogeneity in Baltic Sea whitefish populations revealed by otolith strontium signatures – identification of stocked fish - Hägerstrand Henry; Heimbrand Yvette; Jokikokko Erkki; Florin Ann-Britt; Himberg Mikael; Wiklund Tom; Slotte Joakim; Lill Jan-Olof (Frontiers in Marine Science, 2015)

Estimating the proportion of river and sea spawning whitefish in catches from the brackish Gulf of Bothnia (Baltic Sea) by gill raker counting, genotyping and otolith chemistry analysis - Hägerstrand Henry; Himberg Mikael; Wiklund Tom; Lill Jan-Olof (Frontiers in Marine Science, 2015)